Felicity's Craft Book - Athan, Polly (Pleasant Company Publications Incorporated, 1994)
Learn how to make 16 crafts with Felicity's Craft Book, a kit that includes helpful instructions. Materials are included for three of the projects.
Keywords: Crafts & Hobbies; Juvenile Nonfiction